Advancements in O-Glycosylation Techniques with Diverse Donor Molecules - Samta Singh; Amit Dey; Avinash Tiwari (International Journal of Cheminformatics, 2025)
Since the early stages of carbohydrate chemistry, numerous researchers have employed alkynyl glycosyl donors as key reagents in glycosylation reactions. These donors have played a crucial role in facilitating the synthesis of glycosidic bonds, an essential aspect of carbohydrate-based compounds. Over time, various modifications and improvements have been introduced by different research groups to enhance the efficiency, selectivity, and sustainability of glycosylation processes. A major focus has been on designing glycosyl donors that align with the principles of green chemistry, reducing the reliance on hazardous reagents and improving reaction efficiency. The continuous evolution of alkynyl glycosyl donors has led to innovative approaches that minimize waste, enhance atom economy, and utilize environmentally benign catalysts and solvents. Researchers have explored diverse structural modifications to optimize these donors, improving their reactivity and stability under different reaction conditions. Additionally, advancements in protecting group strategies and activation methodologies have contributed to making these glycosylation reactions more practical and widely applicable in carbohydrate synthesis. Over the past decade, significant progress has been made in this field, with numerous studies reporting novel alkynyl glycosyl donors capable of achieving high yields and excellent stereoselectivity. This review provides an in-depth analysis of the recent developments in alkynyl glycosyl donor chemistry, focusing on their structural diversity, reaction mechanisms, and applications in sustainable glycosylation strategies. By highlighting these advancements, this work aims to provide valuable insights into the future directions and potential applications of these glycosyl donors in carbohydrate synthesis.
Keywords: Glycosyl donor; glycosides; glycosyl acceptor; glycosylation; nucleophilic species